Cytology of lesions arising in and around operative scars: short series of four cases - Shweta D. Ganorkar; Sandhya V. Poflee; Amrapali L. Gaikwad; Nandu P. Pande; Alok C. Shrivastava; Anuradha V. Shrikhande (International Journal of Medical Research and Review, 2015)
Fine needle aspiration cytology (FNAC) is an established and valuable method for morphological diagnosis of soft tissue masses and confirmation of their local recurrence or metastasis. This study aims to highlight role of FNAC in confirmation of soft tissue recurrences that occurred in and around operative scars. Wet fixed & air dried smears were made from the material aspirated from four representative cases and stained routinely. Preoperative cytodiagnosis could be given in all cases. In two cases arising in previous scars of benign nerve sheath tumors, FNAC confirmed recurrence in one case and could suggest increased grade of lesion in the other. In the third case, in which initial nature of the lesion was not known, FNAC diagnosed scar endometriosis on two occasions. In fourth case local recurrence of extra abdominal fibromatosis was confirmed. Histopathological correlation was available in all cases. FNAC confirmed recurrence and could suggest diagnosis on scanty material.